A rare case of Meckel Gruber syndrome - Chandra, Rudrika; Singh, Bhanu Pratap; Singh, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Meckel Gruber syndrome (MGS) is a rare lethal autosomal recessive disorder. It is characterized by triad of features having occipital meningoencephalocele, polycystic kidneys and post-axial polydactyly. We report an antenatal patient detected with occipital meningoencephalocele in foetus on early anomaly scan at 15 weeks of gestation followed by foetal MRI which revealed the typical triad features strongly suggestive of MGS. The patient opted for medical termination of pregnancy and the abortus was autopsied, with the permission of the patient, for detailed evaluation of anomalies which were consistent with MGS. This case highlights the importance of a detailed foetal evaluation antenatally to detect anomalies which are incompatible with life and proper diagnosis as it has bearing on patient’s future obstetric outcome.